Why at the start of the Fourth Industrial Revolution do we see a rise in cult-type Pentecostal churches in South Africa? - Maria Frahm-Arp (The Thinker)
In 2013, we saw one of the first broad-based consumer applications of Article Intelligence in Apple and Smartphone devices that began to predict how we wrote text messages. This was just one example of how the Fourth Industrial Revolution (4IR) began, and how it directly affected our lives. Klaus Schwab, the founder and executive chairman of the World Economic Forum, first coined the term ‘Fourth Industrial Revolution’ to describe the new era of machine and human augmentation and integration. He suggests that this is a time of enormous promise as machines can enhance the way people live, but if we are left behind by this revolution or it is not correctly regulated, it could also be a time of increasing peril for humanity (Schwab 2016).